Ideologies and structures of higher learning institution model: reconstructing the worldview of higher education - Abdul Rahman, Shukran (Islamic Education Programme, Academy of Islamic Studies, University of Malaya, 2017)
The objective of this paper is to discuss the current scenario of higher education system vis-a-vis the diverse ideologies and structures of higher education model. It describes the current orientation of higher education delivery characterized by widely accepted normreferenced higher education performance instead of limited focus on criterion-referenced approaches. The paper also describes a number of higher education best practices in early Islamic and Western institutions, and registers some challenges faced by Muslims in relation to higher education system. It also attempts to chart the way forward for the effort to reconstruct the ‘accepted’ worldview on higher education.